Process of reservoir sedimentation in steep channel (Journal of Nepal Geological Society, 2000)
The process of sedimentation has been studied in a small, steep laboratory flume with a dam, which causes the hydraulic jump in the reservoir. The two-dimensional and three-dimensional bed profiles were observed in experiments with coarse and fine sediment, respectively. The profiles of water surface and sediment deposition are simulated numerically with the application of one-dimensional continuity flow equation and sediment transport. The simulated results coincide well with the observed ones except undulation bed profiles.